Leveraging environment and climate change initiatives for corporate excellence - Venkatachalam Anbumozhi; Mari Kimura; Kumiko Isono (Asian Development Bank Institute (ADBI), 2011)
This paper reviews selected initiatives taken by Asian countries to comply with emerging global sustainability standards, reporting, and management systems, and tracks the response of Asian businesses to global environmental concerns, examines market based innovations including new regulations that augmented corporate excellence, and identifies future directions for business that lead low carbon society. It recommends governments and business to join forces in supporting low carbon initiatives, drawing upon market mechanisms through reconfiguring national environmental policies and strategies.
Keywords: M19; Q3; Q48; Q56; 330; climate change initiatives; global sustainability standards; low carbon initiatives; environmental policies; Klimawandel; Internationale Umweltpolitik; Wirtschaftliche Anpassung; Regulierung; Internationaler Wettbewerb; Asien